Determinants of Tax Avoidance and Audit Quality as a Moderating Variable - Ayunita Ajengtiyas Saputri Mashuri (Ilomata International Journal of Tax and Accounting, 2023)
Taxes is The largest contribution for every country financial forecast. The Government maximizes their effort to be able increasing taxes, in order to accomplish the needs of their people. Companies are one of the biggest expenses of country need to be able to be financed. As a result, the government's efforts can create conflicts and it is not in line with the company's goals it self. The company will try to do a tax avoidance scheme in order to reduce the amount of the tax burden, however it will trigger various problems. Agency theory that can solve those problems that arise, from company as an agent. There are factors impact on tax avoidance, it consists of institutional ownership and corporate social responsibility. Audit quality is taken as a moderating variable, in analyzing the effect between the two independent variables, either strengthens or weakness. This type of research is quantitative research that uses the company's annual report as sources data. The sample in this study amounted to 43 mining companies listed on the Indonesia Stock Exchange in 2017-2019 and were selected based on purposive sampling technique. The results of data testing show that institutional ownership has no significant positive effect on tax avoidance, while corporate social responsibility has a significant positive effect on tax avoidance. Audit quality is showed to be able to weaken the influence of institutional ownership on tax avoidance and strengthen the influence of corporate social responsibility on tax avoidance.